2013
DOI: 10.4103/2230-8210.117212
|View full text |Cite
|
Sign up to set email alerts
|

Emerging risk factors for cardiovascular diseases: Indian context

Abstract: Cardiovascular disease (CVD) is globally considered as the leading cause of death with 80% of CVD related deaths being reported from low and middle income countries like India. The relatively early onset age of CVD in India in comparison to Western countries also implies that most productive ages of the patient's life are lost fighting the disease. Conventional cardiovascular risk is attributed to lifestyle changes and altered metabolic activity. This forms the basis of a 10-year risk prediction score inspired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 58 publications
(78 reference statements)
2
39
1
1
Order By: Relevance
“…Clustering of three or more cardiovascular risk factors was present in 22.7% of the men and 21.7% of the women in South Korea 17. In Malaysia, 33% of the national population had two or more risk factors,18 and similar findings have been reported for India 19…”
Section: Discussionsupporting
confidence: 75%
“…Clustering of three or more cardiovascular risk factors was present in 22.7% of the men and 21.7% of the women in South Korea 17. In Malaysia, 33% of the national population had two or more risk factors,18 and similar findings have been reported for India 19…”
Section: Discussionsupporting
confidence: 75%
“…There are many risk factors which contribute to the present epidemic situation of CVDs in Indian populations. Various studies reported an association of environmental risk factors with the development of CVDs [14, 15]. In our previous study, we presented abdominal obesity, even at normal BMI, dyslipidemia, family history of CAD, and cigarette smoking as independent risk factors for CAD in north Indians [16].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is the leading cause of death worldwide, responsible for over 7 million deaths annually . It is believed that more than 50% of the Indian population will have heart ailments in the next 15 years . In Indians, the disease sets in a decade earlier than their counterparts in developed countries .…”
Section: What Is Known and Objectivementioning
confidence: 99%